Nitrification Is a Primary Driver of Nitrous Oxide Production in Laboratory Microcosms from Different Land-Use Soils - Liu, Rui; Hu, Hangwei; Suter, Helen; Hayden, Helen L.; He, Jizheng; Mele, Pauline; Chen, Deli (Frontiers in Microbiology, 2016)
Most studies on soil N2O emissions have focused either on the quantifying of agricultural N2O fluxes or on the effect of environmental factors on N2O emissions. However very limited information is available on how land-use will affect N2O production, and nitrifiers involved in N2O emissions in agricultural soil ecosystems. Therefore, this study aimed at evaluating the relative importance of nitrification and denitrification to N2O emissions from different land-use soils and identifying the potential underlying microbial mechanisms. A 15N-tracing experiment was conducted under controlled laboratory conditions on four agricultural soils collected from different land-use. We measured N2O fluxes, nitrate (NO3−) and ammonium (NH4+) concentration and15N2O, 15NO3− and 15NH4+ enrichment during the incubation. Quantitative PCR was used to quantify ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB). Our results showed that nitrification was the main contributor to N2O production in soils from sugarcane, dairy pasture and cereal cropping systems, while denitrification played a major role in N2O production in the vegetable soil under the experimental conditions. Nitrification contributed to 96.7% of the N2O emissions in sugarcane soil followed by 71.3% in the cereal cropping soil and 70.9% in the dairy pasture soil, while only around 20.0% of N2O was produced from nitrification in vegetable soil. The proportion of nitrified nitrogen as N2O (PN2O value) varied across different soils, with the highest PN2O value (0.26‰) found in the cereal cropping soil, which was around 10 times higher than that in other three systems. AOA were the abundant ammonia oxidizers, and were significantly correlated to N2O emitted from nitrification in the sugarcane soil, while AOB were significantly correlated with N2O emitted from nitrification in the cereal cropping soil. Our findings suggested that soil type and land-use might have strongly affected the relative contribution of nitrification and denitrification to N2O production from agricultural soils.